2014
DOI: 10.1136/bmjopen-2014-005265
|View full text |Cite
|
Sign up to set email alerts
|

The IDEAL DVT study, individualised duration elastic compression therapy against long-term duration of therapy for the prevention of post-thrombotic syndrome: protocol of a randomised controlled trial

Abstract: IntroductionPost-thrombotic syndrome (PTS) is a serious complication of deep vein thrombosis (DVT) of the leg that affects 20–50% of patients. Once a patient experiences PTS there is no treatment that effectively reduces the debilitating complaints. Two randomised controlled trials showed that elastic compression stocking (ECS) therapy after DVT for 24 months can reduce the incidence of PTS by 50%. However, it is unclear whether all patients benefit to the same extent from ECS therapy or what the optimal durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Based on these findings, a randomized non‐inferiority trial was designed. This trial investigated whether the main therapeutic effect of individualized ECS therapy following initial 6 months of ECS therapy would not be unacceptably different from that of standard duration of therapy, and whether the accepted loss of efficacy of the new therapy would be balanced by a reduction in costs and or an increase in HRQoL . The upper margin of the loss of efficacy that was deemed to be acceptable was set at 7.5% (the noninferiority margin) …”
Section: Barriers To Progress and Future Perspectivessupporting
confidence: 67%
“…Based on these findings, a randomized non‐inferiority trial was designed. This trial investigated whether the main therapeutic effect of individualized ECS therapy following initial 6 months of ECS therapy would not be unacceptably different from that of standard duration of therapy, and whether the accepted loss of efficacy of the new therapy would be balanced by a reduction in costs and or an increase in HRQoL . The upper margin of the loss of efficacy that was deemed to be acceptable was set at 7.5% (the noninferiority margin) …”
Section: Barriers To Progress and Future Perspectivessupporting
confidence: 67%
“…Whether a shorter duration of ECS therapy provides the same benefits for the prevention of PTS still needs to be established. The final results of the IDEAL DVT study will have to be awaited to ensure the safety of individually tailored duration of ECS therapy and its eventual effect on compliance in the long term .…”
Section: Discussionmentioning
confidence: 99%
“…The medical ethical committee of the Maastricht University Medical Centre approved this study, and all patients gave written informed consent. Consecutive patients with proximal DVT are being included in the IDEAL DVT study . In September 2013 the DCE survey was implemented in the study.…”
Section: Methodsmentioning
confidence: 99%
“…The ongoing IDEAL study will investigate whether tailoring compression stocking therapy to individual patients and symptoms would save costs and select for the most appropriate patients who would derive benefit. Results are expected in 2017 (Ten Cate‐Hoek et al , ). Pharmacological therapies for PTS have been explored, however a 2013 Cochrane review found a lack of placebo‐controlled trials in support of rutosides (Morling et al , ), compounds derived from horse chestnut and claimed as herbal remedies for the management of oedema and symptomatology in chronic venous disease.…”
Section: Predictors and Modifiers Of Long‐term Outcomementioning
confidence: 66%